The Marketing Concept, the Elements of Marketing and the Effect of Market Orientation. Research into the market orientation of advertising agencies in Iceland - Sturla Sigurðsson 1969- (2011)
Marketing is defined by the American Marketing Association as "the activity, set of institutions, and processes for creating, communicating, delivering, and exchanging offerings that have value for customers, clients, partners, and society at large". Marketing consists of many smaller disciplines, which together form the field of marketing. A market oriented organization must understand, master and adapt the elements of marketing to its regular activities. Market orientation is the ideology on which market driven organizations base their organization and execution. Market orientation is the heart and cornerstone of modern marketing management and strategy and is the foundation of high-‐quality marketing. Three conceptualizations of a market orientation are most dominant in the literature on market orientation. These are the conceptualizations of Kohli and Jaworski, Narver and Slater, and Day and Sinkula. There are mainly two methods to measure an organization's market orientation. These methods are MARKOR scale by Kohli, Jaworski and Kumar and MKTOR by Narver and Slater. In this research the improved MARKOR scale by Matsuno, Mentzer and Rentz is used. The market orientation of advertising agencies in Iceland was studied. The purpose of the research was to measure the level of market orientation and its relation to each organization's performance compared to its competitors. The results show that there is a positive relationship between market orientation and performance. While the combined market orientation of the participating advertising agencies is higher than that of the insurance market, it can not be described has high. This holds especially true when it is considered that the core business of these organizations is deeply embedded with the marketing concept. The main limitations of the research are the low number of participants from each advertising agency and possible effects of the financial crisis that could have had very different effects on each of the agencies.